Deliberative Democratic Theological Education: A Proposal for Youth Ministry That Builds Peace - Corrie, Elizabeth W. (Religious education, 2020)
Drawing on research in deliberative pedagogy, this paper will develop in depth one piece of a larger project that envisions peace education as an essential component of youth ministry. The paper proposes a sacred pedagogy that engages theological concepts through deliberative, democratic discussion, teaching young people skills in engaging across difference as well as habits of deliberative theological thinking for a lifetime of spiritual growth. The specific example of engaging the problem of how we image Jesus will serve as an illustration of the potential for a series of curricular materials for use in congregational youth settings.